Insulin-like growth factors in cat placenta - Hernández, Rocío (2024)
Placental development involves maternal-fetal signalling events, and it is an under-researched topic in feline reproduction. Few studies of endotheliochorial placentas deal with insulin-like growth factors (IGFs), which are among the principal developmental regulators. While placental expression of IGFs and type 1 IGF receptor (IGF1R) has already been reported in bitches, data regarding the IGF system in queens are limited to uterine tissues. This study aimed to detect IGF1, IGF2, and IGF1R in fetal and maternal placental structures. Samples from twenty-three placentas were classified into one of two groups depending on gestational age (G1: ≤43 d.p.c; G2: ≥44 d.p.c) and processed by indirect immunohistochemistry. Labelling with all the antibodies was stronger in the endometrial glands of earlier placentas than in later ones. Maternal endothelium was moderate to strongly labelled, with a decreasing intensity in the endometrium, while the opposite occurred in the labyrinth. Cytotrophoblast cells were more strongly labelled than the syncytiotrophoblast. IGF1 and IGF1R-positive cells were more abundant in decidual cells of later placentas. These results support that the IGF system plays a central role during gestation and development in cats. As far as we know, this is the first report recording immunohistochemical IGFs/IGF1R detection in fetal regions of the feline placenta.